Application of emulsifiers in chocolate: a short review - Hussain, Norhayati (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
Emulsifiers have long been used to modify the flow properties of chocolate masses, texture, influence sensitivity to relative humidity, temperature, tempering behaviour, susceptibility to fat bloom, stability against fat migration from fillings, and stability against oxidation. These have driven the development of various emulsifiers from various sources (plant/ conventional, chemical and enzymatic method) for application in food. This short review focuses on the role of common emulsifiers applied for improvement of chocolate quality in order to meet the consumers or producers demand.